An empirical investigation of the input substitutability in the inshore and open sea fisheries - Νταούλη, Ιωάννα; Ντεμούσης, Μιχαήλ; Φουσέκης, Π. (SPOUDAI Journal of Economics and Business, 2001)
The knowledge of the internal structure of effort is very important in designing and implementing effort reduction policies in fisheries. In this paper we investigate empirically input substitutability in the open sea and the inshore fleet of Greece using a translog effort production function with four inputs (i.e., labor, consumables, capital and fishing gear). The calculated Allen, Morishima and McFadden elasticities of substitution suggest that there is potential for expansion of unregulated inputs in both sectors of the Greek fleet. This potential however is much greater for the inshore sector. Overall, the empirical results indicate that policies which target a relative large subset of fishing inputs are required to achieve the goals of stock preservation and economic efficiency. JEL Classification: Q20, Q22